الزراعة الذكية مناخيا و تغير المناخ - غدامسي, عائشة (جامعة الوادي - University of Eloued, 2018)
يؤثر القطاع الزراعي ويتأثر بتغير المناخ، ومن أجل تقليص حجم الأثر المتبادل بينهما ظهر ما يعرف بالزراعة الذكية مناخيا، و يهدف هذا البحث إلى إعطاء فكرة أوسع عن هذا المفهوم كوسيلة لمواجهة آثار تغير المناخ على القطاع الزراعي والأمن الغذائي، كما يهدف كذلك إلى توضيح مختلف المزايا التي يتيحها تطبيق الممارسات الزراعية الذكية مناخيا من خلال عرض تجربتين إفريقيتين في هذا المجال هما كينيا و أثيوبيا The agricultural sector affects and is being affected by climate change, and to reduce the extent of mutual impact between them climate-smart agriculture emerged. The aim of this research is to give a broader idea of this concept as a means of addressing the impacts of climate change on the agricultural sector and food security. It also aims at clarifying the various advantages that the application of climate-smart agricultural practices offers by presenting two African experiences in this field, namely Kenya and Ethiopia.
مقال
Keywords: القطاع الزراعي، تغير المناخ، الزراعة الذكية مناخيا، كينيا، إثيوبيا. Agricultural sector - climate change – climate smart agriculture – Kenya – Ethiopia.